Key Role of Astrocytes in Postnatal Brain and Retinal Angiogenesis - Mariela Puebla; Pablo J. Tapia; Hilda Espinoza (My University, 2022)
Angiogenesis is a key process in various physiological and pathological conditions in the nervous system and in the retina during postnatal life. Although an increasing number of studies have addressed the role of endothelial cells in this event, the astrocytes contribution in angiogenesis has received less attention. This review is focused on the role of astrocytes as a scaffold and in the stabilization of the new blood vessels, through different molecules release, which can modulate the angiogenesis process in the brain and in the retina. Further, differences in the astrocytes phenotype are addressed in glioblastoma, one of the most devastating types of brain cancer, in order to provide potential targets involved in the cross signaling between endothelial cells, astrocytes and glioma cells, that mediate tumor progression and pathological angiogenesis. Given the relevance of astrocytes in angiogenesis in physiological and pathological conditions, future studies are required to better understand the interrelation between endothelial and astrocyte signaling pathways during this process.
Keywords: brain angiogenesis; retinal angiogenesis; astrocytes; endothelial cells; extracellular matrix; astrocytes; brain; endothelial cells; humans; neovascularization, pathologic; neovascularization, physiologic; retina; adam10 endopeptidase; alpha beta5 integrin; alpha beta8 integrin; angiopoietin 1; angiopoietin receptor; astrocyte elevated gene 1; beta1 integrin; cytochrome p450; epoxyicosatrienoic acid; fibroblast growth factor 2; fibroblast growth factor receptor 1; fibroblast growth factor receptor 2; fibroblast growth factor receptor 3; fibronectin; focal adhesion kinase; glial fibrillary acidic protein; hypoxia inducible factor; hypoxia inducible factor 1; hypoxia inducible factor 2alpha; integrin; laminin; leukemia inhibitory factor; mammalian target of rapamycin; matrix metalloproteinase; membrane protein; messenger rna; meteorin; mitogen activated protein kinase; mitogen activated protein kinase 1; mitogen activated protein kinase 3; mitogen activated protein kinase kinase 1; nerve cell adhesion molecule; nr2f2 protein; orphan nuclear receptor; p cadherin; phosphatidylinositol 3 kinase; platelet derived growth factor; protein kinase b; protein p53; r cadherin; ras protein; rhoa guanine nucleotide binding protein; stat3 protein; t cadherin; thrombospondin 1; thrombospondin 2; tie 1 receptor; transcription factor yap1; transforming growth factor beta; unclassified drug; vascular endothelial cadherin; vasculotropin; vasculotropin receptor 2; very late activation antigen 5; angiogenesis; astrocyte; astrocytoma; brain; brain cancer; brain development; cell adhesion; cell migration; cell proliferation; cell survival; crispr-cas9 system; endothelium cell; enzyme activation; fibroblast; gene overexpression; glioblastoma; glioma cell; homeostasis; human; macrophage; microglia; morphogenesis; neuroblast; nonhuman; oligodendroglia; pericyte; perinatal period; phenotype; retina; review; signal transduction; tumor growth; tumor microenvironment; angiogenesis